Are China and the United States in a Competitive Zero-Sum Economic Game?. Issue 5 (19th October 2016) - Hartman, Stephen W.; Whooley, Peter
ABSTRACT: China has implemented a model of state capitalism while the growth of the United States in the same time period occurred using a market-driven liberalism model. While evidence indicates that China's state-owned companies are less innovative and productive than their private competitors, China's control pattern of free-market competition has been amazingly successful. This article shows that there are distinct differences between China's state capitalism model and the U.S. economic model. China and the U.S. are not competitors in a zero-sum game. The dynamic between the American and Chinese economies continues to develop into a more mature relationship than an outright competition.